Democratic parenting in developing Emotional Intelligence and Youth Religiosity in Kramatagung Probolinggo - Khosiah , Nur; Dheasari , Agustiarini Eka; Abidin , Zainal (Al-Insyiroh: Jurnal Studi Keislaman, 2021)
Education for children starts from family because it will determine the character of children in adolescence. The purpose of this study is to determine the role of democratic parenting in building emotional intelligence and religiosity in adolescents. Because without parental guidance the child will experience deviations in the daily behavior. The research subject was in Kramatagung Village, Bantaran District, Probolinggo. In this case, the researcher used descriptive qualitative methods. Observation, interviews, and documentation were used in the data collection techniques and to analyze the data the researcher used data reduction, data presentation, and drawing conclusions techniques. This research showed that the emotional intelligence and religiosity of adolescents in Kramatagung village are categorized as poor, but parents in implementing parenting styles for children in Kramatagung village are quite democratic. Furthermore, based on research it is known that the emotional intelligence and reliability of adolescents in the Kramatagung village are quite an apprehension. The adolescents who are emotionally intelligent and have good religious intelligence are educated by applying democratic parenting. It is the duty of parents to educate, guide, nurture, and always remind also advise the children not to be trapped by world life which increasingly shows freedom in an association. Guidance and education especially in the family are top priorities in addition to other education outside the home